THE RELATIONSHIP BETWEEN URIC ACID LEVELS AND THE OCCURRENCE OF BENIGN PAROXYSMAL POSITIONAL VERTIGO - Adi Putra, Kiking Ritarwan & Kiki M. Iqbal (International Journal of Research Science and Management, 2020)
Background: Benign Paroxysmal Positional Vertigo (BPPV) is associated with a fundamental condition that causes the release of large amounts of otoconia, due to deficits in the structure of the interotoconial filament matrix which implants otoconia in the gelatinous matrix. Increased uric acid levels cause an inflammatory response in the gelatinous matrix so that it can cause BPPV attacks. Objective: To determine the relationship between uric acid levels with BPPV events Research Methods: This research uses a case control design. Sampling was conducted at H. Adam Malik General Hospital Medan and RS. University of Sumatera Utara. The research sample consisted of 36 BPPV cases and 36 non BPPV cases. subject on a consecutive basis. Anamnesis and physical examination are performed to diagnose BPPV and examination of uric acid levels for hyperuricemia status. Data analysis using chi-square test Results: The majority of BPPV patient characteristics were found in women (63,9%), age range 41-50 years (36,1%), high school education level (33,3%), working as a housewife (30,6%), and Batak ethnicity (69,4%). The distribution of uric acid levels in BPPV patients was 6.59 (± 1.30) mg / dl. The distribution of hyperuricemia of BPPV patients was 58.3%. There is a significant relationship between uric acid levels with BPPV events. (p = 0.033; OR = 3.18). Conclusion: there is a significant relationship between uric acid levels with BPPV.